Risk of venous thromboembolism with janus kinase inhibitors in inflammatory immune diseases: a systematic review and meta-analysis - Juqi Zhang; Juqi Zhang; Juqi Zhang; Wenhui Li; Wenhui Li; Wenhui Li; Mingli Gong; Yanlun Gu; Yanlun Gu; Yanlun Gu; Hanxu Zhang; Hanxu Zhang; et al. (Frontiers Media S.A., 2023)
Objectives: This study aimed to evaluate the risk of venous thrombosis (VTE) associated with Janus kinase (JAK) inhibitors in patients diagnosed with immune-mediated inflammatory diseases.Methods: We conducted a comprehensive search of PUBMED, Cochrane, and Embase databases for randomized controlled trials evaluating venous thromboembolic incidence after administering JAK inhibitors in patients with immune-mediated inflammatory diseases. The studies were screened according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and a meta-analysis was performed.Results: A total of 16 studies, enrolling 17,242 participants, were included in this review. Four approved doses of JAK inhibitors were administered in the included studies. The meta-analysis revealed no significant difference in the incidence of VTE between patients receiving JAK inhibitors, a placebo, or tumor necrosis factor (TNF) inhibitors (RR 0.72, 95% CI (0.33-1.55); RR 0.94, 95%CI (0.33-2.69)). Subgroup analysis showed a lower risk of VTE with lower doses of JAK inhibitors [RR 0.56, 95%CI (0.36-0.88)]. Compared with the higher dose of tofacitinib, the lower dose was associated with a lower risk of pulmonary embolism [RR 0.37, 95%CI (0.18-0.78)].Conclusion: Our meta-analysis of randomized controlled trials observed a potential increase in the risk of VTE in patients with immune-mediated inflammatory diseases treated with JAK inhibitors compared to placebo or tumor necrosis factor inhibitors, though statistical significance was not attained. Notably, a higher risk of pulmonary embolism was observed with high doses of tofacitinib. Our findings provide valuable insights for physicians when evaluating the use of JAK inhibitors for patients with immune-mediated inflammatory diseases.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023382544, identifier CRD42023382544